6G R&D Vision: Requirements and Candidate Technologies - Hong, Een Kee; Lee, Inkyu; Shim, Byonghyo; Ko, Young Chai; Kim, Sang Hyo; Pack, Sangheon; Lee, Kyunghan; Kim, Sunwoo; Kim, Jae Hyun; Shin, Yoan; Kim, Younghan; Jung, Haejoon (Journal of Communications and Networks, 2022)
—The Korean Institute of Communications and Information Sciences (KICS), which is the largest information and communication technology institute in Korea, has been active in working towards development and standardization of mobile communication technology. In response to the need to meet upcoming 6G technical challenges in innovative applications such as hologram telepresence, extended reality (XR), digital twin, and connected robotics, the KICS 6G research initiative (KICS 6GRI) group has been created to establish a vision for key 6G technologies and identify research trends and directions. This article, therefore, covers major performance indicators and requirements envisioned by the KICS. In addition, we provide a comprehensive discussion of various candidate 6G technologies including (sub-)terahertz (THz), intelligent reflecting surface (IRS), artificial intelligence (AI)-based techniques, and non-terrestrial network (NTN).
Keywords: 6g; D-vision; Information and Communication Technologies; Mobile communication standards; Mobile communication technology; Research initiatives; Research trends; Technical challenges; Telepresence; The korean institute of communication and information science; 6G; mobile communication standard; the Korean Institute of Communications and Information Sciences (KICS)